2017
DOI: 10.1016/j.ehj.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute triggers of myocardial infarction: A case-crossover study

Abstract: BackgroundAcute myocardial infarction (AMI) is one of the most preventable non-communicable diseases in human. Identifying triggers of myocardial infarction (MI) and prevention ways of exposure-induced complications can reduce morbidity and mortality in people at risk.AimThe aim of this study was to identify the emotional, environmental, physical and chemical dimensions of acute triggers in patients with AMI.MethodsThis case-crossover study was conducted on 269 patients with AMI, hospitalized at two remedial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Contrary to that, a case-crossover study of 250 incident acute myocardial infarction cases in Switzerland found no evidence that the effect of binge drinking was significant [ 38 ]. Also, a recent a case-crossover study in Iran showed that alcohol abuse was not an acute trigger associated with significantly increased risk of myocardial infarction [ 39 ]. Possible explanations for the differences in results of these studies could include differences both in the characteristics of respondents (in terms of age, gender, occupation, comorbidity) and in the study design (in terms of the differences in selection of the cases with myocardial infarction and their controls, choice of the reference category for assessment of alcohol consumption, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to that, a case-crossover study of 250 incident acute myocardial infarction cases in Switzerland found no evidence that the effect of binge drinking was significant [ 38 ]. Also, a recent a case-crossover study in Iran showed that alcohol abuse was not an acute trigger associated with significantly increased risk of myocardial infarction [ 39 ]. Possible explanations for the differences in results of these studies could include differences both in the characteristics of respondents (in terms of age, gender, occupation, comorbidity) and in the study design (in terms of the differences in selection of the cases with myocardial infarction and their controls, choice of the reference category for assessment of alcohol consumption, etc).…”
Section: Discussionmentioning
confidence: 99%
“…2 Extreme events weather are known to contribute to an increase in morbidity and mortality, particularly in vulnerable groups(eg, the elderly, children, and people with chronic diseases). 3,4 From 1999 to 2009, 7233 heat-related deaths occurred in the United States. 5 The evaluations of the relevance between metrological variables, such as temperature, and health can help identify mitigation and prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…7 The CVDs—including coronary heart disease and other heart diseases—are the most preventable noncommunicable diseases worldwide. 3,8 The CVDs are highly sensitive to weather variations. Many studies have reported that both cold and hot temperatures had adverse effects on cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial ischemia may occur after physical activity [28,29]. For instance, a previous study suggests that there is a 5.7-fold increase in the risk of acute MI immediately or within 2 h of vigorous physical exertion [30,31] and a 1.6-fold increase in the risk of acute MI immediately or within 2 h of moderate physical exertion compared to rest or low-intensity activities [30].…”
Section: Discussionmentioning
confidence: 99%